Motivation types of volunteers, their personality traits and subjective well-being - Zager-Kocjan Gaja; Podobnik Blaž; Avsec Andreja (Psihologija, 2024)
Using a person-centered approach, this study sought to identify motivation types of volunteers based on their pattern of motives for volunteering and to compare volunteer types in terms of personality and subjective well-being. A two-step cluster analysis conducted on a sample of 441 volunteers revealed four clusters: integrated high function (high on all motives); integrated low function (low on all motives); self-oriented (primarily motivated to advance own career); other-oriented (primarily motivated to pursue values to help others). The other-oriented and the integrated high function clusters reported the highest levels of extraversion, agreeableness, and openness. While satisfaction with volunteering, subjective well-being, and satisfaction of the needs for relatedness and competence were highest in the integrated high function cluster, the other-oriented cluster exhibited the highest satisfaction of the need for autonomy. Our results complement the dimensional approaches to volunteer motivation and show that optimal motivation is achieved by pursuing multiple motives.